Educational Experiences in Religious Moderation at Indonesian Islamic Universities: A Phenomenological Study - Nurul Afifah; Asep Yudianto; Ning Setio Wati; Dian Eka Priyantoro (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
Radicalization has entered the realm of education. Fundamentalist doctrines and movements have prepared students as their successors. Campuses are used as a medium for transnational ideologies to enter, which results in the rejection of the Pancasila ideology. Students with minimal religious knowledge are the main targets. This study aims to explore how religious moderation is actualized and strengthened among students of the State Islamic University (UIN) Jurai Siwo Lampung and the Islamic Institute of Islamic Religion Sunan Giri Ponorogo in responding to the increasing concerns of the influence of radicalism in higher education. Using a qualitative phenomenological approach, data is collected through in -depth interviews with college leaders, from the Chancellor to the Chair of the Study Program and its staff, as well as active students. In addition, observations were made on the understanding and attitude of religious moderation and the study of campus documentation. The findings reveal two primary modes of religious moderation implementation: (1) formal integration through curriculum content and the establishment of religious moderation centers, and (2) informal or hidden curriculum through cross-course character formation and lecturer role modeling. These efforts reflect a strategic response to preserve inclusive Islamic values and counter extremist narratives. The study recommends institutionalizing religious moderation pedagogies to support the vision of Islam as a religion of peace and compassion.